2018
DOI: 10.1007/s11064-018-2618-4
|View full text |Cite
|
Sign up to set email alerts
|

NR4A1 Promotes Cerebral Ischemia Reperfusion Injury by Repressing Mfn2-Mediated Mitophagy and Inactivating the MAPK–ERK–CREB Signaling Pathway

Abstract: Mitochondrial dysfunction has been acknowledged as the key pathogenic mechanism in cerebral ischemia-reperfusion (IR) injury. Mitophagy is the protective system used to sustain mitochondrial homeostasis. However, the upstream regulator of mitophagy in response to brain IR injury is not completely understood. Nuclear receptor subfamily 4 group A member 1 (NR4A1) has been found to be associated with mitochondrial protection in a number of diseases. The aim of our study is to explore the functional role of NR4A1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 52 publications
2
31
0
Order By: Relevance
“…Furthermore, in Nr4a1-deficient cells, blockage of the MAPK-ERK-CREB signaling pathway decreased the levels of Mfn2 and no longer allowed apoptotic inhibition. In sum, this study points to an important role of Mfn2 and of the MAPK-ERK-CREB pathway in the brain, by controlling mitophagy and apoptosis upon IR injury (Zhang and Yu, 2018). The importance of MFN2 in the interplay between mitophagy and apoptosis was confirmed in the context of coronary heart disease, however instead involving the AMPK-CREB pathway (Li P. et al, 2020).…”
Section: Interplay Between Mitochondrial Fusion Mitophagy and Apoptosismentioning
confidence: 57%
See 1 more Smart Citation
“…Furthermore, in Nr4a1-deficient cells, blockage of the MAPK-ERK-CREB signaling pathway decreased the levels of Mfn2 and no longer allowed apoptotic inhibition. In sum, this study points to an important role of Mfn2 and of the MAPK-ERK-CREB pathway in the brain, by controlling mitophagy and apoptosis upon IR injury (Zhang and Yu, 2018). The importance of MFN2 in the interplay between mitophagy and apoptosis was confirmed in the context of coronary heart disease, however instead involving the AMPK-CREB pathway (Li P. et al, 2020).…”
Section: Interplay Between Mitochondrial Fusion Mitophagy and Apoptosismentioning
confidence: 57%
“…The role ERK-MFN2 in mitophagy was also described in cerebral ischemia-reperfusion (IR) injury (Zhang and Yu, 2018). Here, decreased mitophagy and increased apoptosis are associated with brain damage.…”
Section: Interplay Between Mitochondrial Fusion Mitophagy and Apoptosismentioning
confidence: 93%
“…Excessive mitophagy reduced mitochondrial quality which, in turn, caused energy shortage and mitochondrial dysfunction [145]. Furthermore, blockade of the MAPK-ERK-CREB signaling pathway upregulated NR4A1 and repressed Mfn2-mediated mitophagy, thus expanding the area of cerebral infarction and increasing neuronal apoptosis [181]. In cardiomyocytes, damaged mitochondria are sequestered in rab5-positive early endosomes via the ESCRT mechanism, which depends on Parkin, and the loss of rab5 function increases the susceptibility of embryonic fibroblasts and cardiomyocytes to cell death [182].…”
Section: Signaling Pathwaysmentioning
confidence: 99%
“…autophagy is a process that maintains the homeostasis of the microenvironment inside cells via non-selective degradation and phagocytosis of abnormal organelles, proteins and lipids in the cytoplasm (18,19). Mitofusin 2 (Mfn2)-mediated mitophagy is a process by which cells selectively remove damaged or dysfunctional mitochondria via autophagy to maintain the balance between mitochondrial quantity and quality (20)(21)(22). numerous studies have confirmed that Mfn2-mediated mitophagy plays a crucial role in tumor origin, homeostasis, invasiveness and drug resistance (23,24).…”
Section: Introductionmentioning
confidence: 99%